Reduced RVSWI Is Associated With Increased Mortality in Connective Tissue Disease Associated Pulmonary Arterial Hypertension - Clapham, Katharine R.; Highland, Kristin B.; Rao, Youlan; Fares, Wassim H. (Frontiers in Cardiovascular Medicine, 2020)
Rationale: The prognosis of pulmonary arterial hypertension is poor, especially amongst patients with connective tissue disease related pulmonary arterial hypertension. Right ventricular contractility is known to be decreased in scleroderma related pulmonary arterial hypertension. However, it is not known whether intrinsic right ventricular dysfunction is seen in a general CTD population. Objectives: In this study of a large cohort of patients with pulmonary arterial hypertension with multi-year follow-up, we sought to examine the association of measurements of right ventricular function with survival in connective tissue disease associated pulmonary arterial hypertension. Methods: Clinical characteristics of a deidentified cohort of 845 patients with pulmonary arterial hypertension were compared between patients with and without connective tissue disease. The Kaplan-Meier method was used to examine the survival of patients over more than 4 years. The association between right ventricular stroke work index and mortality was examined in patients with connective tissue disease associated pulmonary arterial hypertension. Measurements and Main Results: Significant differences in the 6-min walk distance, Borg dyspnea index, right ventricular stroke work index, and pulmonary artery pulsatility index were identified between patients with and without connective tissue disease associated pulmonary arterial hypertension. Patients with connective tissue disease had a lower right ventricular stroke work index, which was associated with decreased survival in this group; this association approached significance when adjusting for age and renal function. Conclusions: Right ventricular dysfunction as measured by right ventricular stroke work index is associated with decreased survival in patients with connective tissue disease associated pulmonary arterial hypertension despite similar pulmonary vascular resistance. These findings are suggestive of intrinsic right ventricular function in connective tissue disease associated pulmonary arterial hypertension that has a negative impact on the long-term survival of these individuals.